Tworzenie wartości przedsiębiorstwa z perspektywy informacji o kliencie - Gawron, Iwona (Building company value from the perspective of information about customers, 2006)
Company’s value and markel position depends to a high degree on the positive, long-term relations with its customers. This is why companies earmark significant funds for developing those information sources that will help them identify their customers’ tastes and preferences. This article draws the reader’s attention to the fact that customers arc no longer treated as a single target, but arc perceived as an investment in the creation process of a company’s value and future. The article also presents the use of customer information sources in Polish companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 93-102